2012
DOI: 10.1007/s11033-012-2321-5
|View full text |Cite
|
Sign up to set email alerts
|

Renoprotective effects of berberine and its possible molecular mechanisms in combination of high-fat diet and low-dose streptozotocin-induced diabetic rats

Abstract: Berberine (BBR), an effective compound of Chinese traditional herbal medicine, has preventive effects on diabetes and its complications. In this study, we investigated the therapeutic effects and underlying molecular mechanisms of BBR in rats with high-fat diet and streptozotocin (STZ)-induced diabetic nephropathy model. BBR (50, 100, 200 mg/kg/d) were orally administered to male Sprague-Dawley rats after STZ injection and conducted for 8 weeks. Renal damage was evaluated by kidney weight to body weight ratio … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
29
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 51 publications
3
29
0
Order By: Relevance
“…15,39 In the present study we evaluated the renoprotective effect of BBR in DN and found that treatment of DN rats with 100 and 200 mg/kg BBR for 6 weeks significantly increased renal β-arrestin 1 and β-arrestin 2 expression in DN rats. Together with findings from previous studies, 40 these observations lead us to conclude that βarrestin 1 and β-arrestin 2 levels are negatively correlated with ICAM-1 and VCAM-1 expression. Together, the results indicate that BBR has desirable protective effects on the kidney, which are likely related to the downregulation of ICAM-1 and VCAM-1 expression and upregulation of β-arrestin 1 and β-arrestin 2 in the kidneys of DN rats.…”
Section: Discussionsupporting
confidence: 83%
“…15,39 In the present study we evaluated the renoprotective effect of BBR in DN and found that treatment of DN rats with 100 and 200 mg/kg BBR for 6 weeks significantly increased renal β-arrestin 1 and β-arrestin 2 expression in DN rats. Together with findings from previous studies, 40 these observations lead us to conclude that βarrestin 1 and β-arrestin 2 levels are negatively correlated with ICAM-1 and VCAM-1 expression. Together, the results indicate that BBR has desirable protective effects on the kidney, which are likely related to the downregulation of ICAM-1 and VCAM-1 expression and upregulation of β-arrestin 1 and β-arrestin 2 in the kidneys of DN rats.…”
Section: Discussionsupporting
confidence: 83%
“…Analysis of the diabetes complication control trial showed that hypercholesterolemia is associated with an increased albumin excretion rate (40). Experimental animal models using mice, rats, and pigs have shown that high-fat feeding to diabetic animals is associated with accelerated development of albuminuria, mesangial matrix expansion, and glomerular hypertrophy (41)(42)(43)(44). Although the mechanism is unknown, studies have shown that increased oxidized low density lipoprotein induces podocyte retraction and albumin permeability (45).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, BBR has been widely used to treat diabetes and its complications 23,24. BBR treatment may restore the renal functional parameters, improve the glucose and lipid metabolism disorders, and suppress alterations of histologic and ultrastructural changes in the kidney 25. Moreover, BBR inhibits mesangial cell proliferation and extracellular matrix accumulation induced by high glucose (HG) and ameliorates tubulointerstitial fibrosis in DN, which suggests that BBR can be used as a potential drug for DN 2630.…”
Section: Introductionmentioning
confidence: 99%